Neural mechanisms of perceptive and affective processing of body stimuli in anorexia nervosa – are there developmental effects?. (April 2020) - Horndasch, Stefanie; Rösch, Julie; Kratz, Oliver; Vogel, Anne; Heinrich, Hartmut; Graap, Holmer; Moll, Gunther H.; Dörfler, Arnd; Forster, Clemens
Highlights: Patients with anorexia nervosa (AN) and controls process body pictures differently. Activation of regions involved in perception and evaluation is reduced in AN. Integration of visual and body perception with emotions might be impaired in AN. Developmental effects in body processing can be found. Abstract: Different components of body image processing seem to be reflected by different neural mechanisms. A core symptom of Anorexia nervosa (AN) is a disturbance of body image with correlates found on a neural level. The present study focuses on the neural processing of visual body stimuli of different weight categories in adolescent and adult AN patients. Thirty-three adolescents aged 12–18 years (15 AN patients, 18 control participants) and 36 adult women (19 AN patients, 17 control participants) underwent functional magnetic resonance imaging (fMRI) while performing a perceptive and an affective body image task involving photographic stimuli of women belonging to different BMI categories. Differential effects on activation, depending on the BMI of the women shown in the pictures, were found in frontal brain regions, the thalamus, the caudate and the fusiform gyrus. Group effects differentiating between AN patients and control participants were seen mainly in the caudate and insula. No significant developmental effect was seen. During a perceptive task, diminished activation of regions involved in perceptive and evaluative functions as well as emotional reasoning was seen in AN. During an affective task there was a tendency towards activation differences reflecting reduced ability of size estimation and impaired integration of visual and body perception with emotions.